PEMANFAATAN PLATFORM MEDIA SOSIAL DALAM MERESPON KRISIS KOMUNIKASI: STRATEGI PUBLIC RELATIONS PT. PLN PADA KASUS PEMADAMAN LISTRIK SULAWESI SELATAN - Irwanto Irwanto; Hafied Cangara (Fakultas Ilmu Sosial dan Ilmu Politik, 2024)
The power outage in South Sulawesi has become a widely discussed case in the media today. Based on this case, it reflects the complexity of challenges faced by PT. PLN and the importance of a quick and coordinated response from Public Relations (PR) to manage the communication crisis that can influence the public's perception of the company. The author considers it crucial to conduct research related to the crisis conditions and crisis communication strategies to be undertaken by PR of PT. PLN. Public Relations of PT. PLN can leverage social media platforms as part of the PR strategy in responding to the communication crisis related to power outages in South Sulawesi. An exploratory qualitative methodology is employed. Data collection methods involve literature review, observation, and case studies. The utilization of social media in crisis communication, applying the STREMII (STREAM-ee) model by Stewart and Wilson, introduces a cyclical process for organizations as a reference when engaging in crisis communication using social media platforms. The six related elements of STREMII include: (a) social monitoring and listening, (b) targeting the right audience, (c) crisis response and conversation, (d) monitoring environmental conditions and evaluating outcomes, (e) interacting with consumers and the public, and (f) implementing necessary changes.